ANALYSIS OF FACTORS CHARACTERISTICS OF CULTURE ORGANIZATION ON EMPLOYEE PERFORMANCE - Frans Papilaya (Universitas Musamus,Merauke,Papua, 2015)
This study aims to determine the influence of the characteristics For culture organizational on employee performance PDAM Merauke.dengan using data analysis technique in which quantitative techniques are used to test the effect of independent variables and the dependent variable.The statistical method used is to use simple regression: The formula used is Y = a + b1x1 + b2X2 + b3X3 + b4X4 + b5X5 + e. The technique of data processing is done is composed of six variables. The sixth variable is adopted from instruments that are formulated using scoring techniques. Scoring techniques in this study is